Direct medical costs associated with the extrahepatic manifestations of hepatitis C virus infection in France. Issue 1 (18th October 2017) - Cacoub, P.; Vautier, M.; Desbois, A. C.; Saadoun, D.; Younossi, Z.
Summary: Background: The economic impact of extrahepatic manifestations of hepatitis C virus (HCV) infection remains unknown for France. Aim: To estimate the prevalence of extrahepatic manifestations of HCV and the direct medical costs associated with them. Methods: Estimates of 13 extrahepatic manifestations prevalence were obtained from (1) a retrospective data analysis of HCV‐infected patients in a specialised centre and the baseline prevalence in the general French population and (2) an international systematic review. Per‐patient‐per‐year costs to treat these manifestations were obtained from the literature, national databases or expert opinion. The impact of achieving HCV cure after anti‐viral therapy was applied to the French healthcare costs. Results: Using approach (1), increased prevalence rates in HCV patients compared to the general population were observed for most extrahepatic manifestations. The mean per‐patient‐per‐year cost of these manifestations in the tertiary centre was 3296 € [95% CI 1829; 5540]. In France, HCV‐extrahepatic manifestations amounted to a total cost of 215 million (M) € per year [144; 299]. Using approach (2), the mean per‐patient‐per‐year cost was estimated to be 1117 €. The estimated total cost reduction in France associated with HCV cure was 13.9 M€ for diabetes, 8.6 M€ for cryoglobulinemia vasculitis, 6.7 M€ for myocardial infarction, 2.4 M€ for end‐stage renal disease and 1.4 M€ for stroke. Conclusion: Extrahepatic manifestations of HCV infection substantially add to the overall economic burden of the disease in France. HCV cure after anti‐viral therapy is expected to significantly reduce the total costs of managing these manifestations in France.